Planning of Units and Program Quality Mapping in PKBM in West Java - Komar, Oong; Heryanto, Nunu; Sukmana, Cucu (Universitas Negeri Jakarta, 2023)
The implementation of the quality mapping program for PKBM units answers the facts of problems that often occur in every non-formal institution, in particular, problems in institutional operations. Based on the preliminary study, the reasons that often emerge raised by PKBM managers are the need for costs for institutional operations, the competence of educators who do not understand the andragogical approach to the implementation of learning, then the concern of the government in the world of non-formal education. Through this study, trying to create based on the analysis of community needs. This study aims to describe the quality management of the PKBM units and programs that emphasize the principles of managing community education programs. To reveal the data and information, the researcher applied a descriptive study with a qualitative approach, which was to reveal the depth of data and information based on the research formulation and the research questions to be revealed, namely how to manage the quality mapping of units and the PKBM program. Program management is divided into three stages, namely, the planning, implementation, and evaluation stages. Of the three stages in its implementation, it always begins with analyzing needs, then compiling a recommended forum design with the development of discussion materials, then ending with an evaluation